The Impact of Reaction Lights-Based Shadow Training on Foot Agility in Badminton Players at Pelangi Pontianak City - Rahmat, Ade; Cahyadi, Ashadi (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2024)
The purpose of the study. The purpose of this study was to find out the effect of reaction light trainingand shuttle run on footwork agility in PB badminton participants Pelangi Pontianak City. Materials and methods. This study uses this type of experimental research. Inthis study there were two groups of experiments that were deliberately given treatment. Results. The analysis's findings for the first test's Lscore test count and the test's final result were Lcalculated, yielding 0.1866<Ltable 0.2287 and 0.1356<Ltable 0.2287. Thus, based on the analysis of this data, preliminary test results and final tests of the normal distribution can be drawn. The sample size of 15, mean 2.75, standard deviation 1.02, and thitung 10.43 are used to determine whether the H0 or Ha hypothesis is accepted in line with the previously given explanation, after which the price calculated and the price of table t are compared. Price comparison between tcalculates to a genuine degree α = 0.05 with degrees of freedom (dk) = (n–1) = 14 and presentil values on the distribution table-t; the result was tcount (10.43)>ttable (1.7613). Conclusions. There is an effect of training using reaction light tools and shuttle run exercises in improving the agility of footwork (footwork) of PB Pelangi Pontiank City Achievement with tCalculate>tTable Can be taken the decision that there is an effect of training using reactionlights and shuttle run exercises in improving.